1984
DOI: 10.1289/ehp.8456187
|View full text |Cite
|
Sign up to set email alerts
|

Histogenesis of pancreatic carcinogenesis in the hamster: ultrastructural evidence.

Abstract: Pancreatic carcinogenesis in the Syrian hamster, induced by 3-oxidized derivatives of N-nitroso-di-npropylamine, constitutes a valuable model of human cancer of the exocrine pancreas. In both species the majority of tumors are adenocarcinomas: superficially, on the basis of their histological appearance, these appear to be ductal in origin. However, sequential analysis, by electron microscopy, of the development of pancreatic neoplasia in the hamster model indicates that acinar cells may participate in the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Ultrastructural studies suggest that the earliest lesions in a hamster cancer model involve the centroacinar cells or cells of acinar origin. 36,37 In this model there is evidence that centroacinar cells are the origin for tubular formations. Early neoplastic features are hypertrophy and hyperplasia of centroacinar cells, which form initially tiny and long processes that overlie and underlie the adjacent acinar cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural studies suggest that the earliest lesions in a hamster cancer model involve the centroacinar cells or cells of acinar origin. 36,37 In this model there is evidence that centroacinar cells are the origin for tubular formations. Early neoplastic features are hypertrophy and hyperplasia of centroacinar cells, which form initially tiny and long processes that overlie and underlie the adjacent acinar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early neoplastic features are hypertrophy and hyperplasia of centroacinar cells, which form initially tiny and long processes that overlie and underlie the adjacent acinar cells. 37…”
Section: Discussionmentioning
confidence: 99%
“…In two recently published series, CEA and CA19-9, which are well known markers of pancreatic ductal adenocarcinomas [7,19], were found to be positive in 18% [14] and 41% [8] of ACCs, respectively. Ductal differentiation within ACCs, sometimes considered as mucous metaplasia of turnout cells [5], probably reflects the capacities of ACCs for differentiating into several directions, including ductally [8].…”
Section: Discussionmentioning
confidence: 99%
“…Wiedenman et al [33] demonstrated immunohistochemically and electron microscopically coexpression of zymogen granules and neuroendocrine vesicles in the cells of a rat acinar carcinoma [5], which seems to be amphicrine in origin. Scattered neuroendocrine cells are encountered in approximately 40% of human ACCs [8,14], but the unequivocal immunocytochemical demonstration of exocrine (pancreatic enzymes) and neuroendocrine markers in the same turnout cells is infrequent [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggests that the formation, growth or progression of tubular ductal complexes to carcinomas can be stimulated by injections of CCK. 16 The development of hepatocyte like foci within the pancreas of carcinogen treated hamsters and rats has been characterised in the hamster by Rao et al,6 and seems to be a florid metaplastic change of acinar or ductal cells that reflects the close embryonic relation-ship of the pancreas and liver. Hepatocyte like foci seem to have low growth potential and no carcinoma of this cell type has been described in hamster pancreas.…”
Section: Neoplastic Growthmentioning
confidence: 99%